Teknik Pemeriksaan Radiografi Wrist Joint pada Kasus Fraktur di Instalasi Radiologi RSU PKU Muhammadiyah Delanggu - Tira Arini; Anisa Nur Istiqomah; Ayu Mahanani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Radiographic examination of the wrist plays a crucial role in diagnosing fractures, particularly in traumatic cases, and requires precise projection selection, proper immobilization, and adequate radiation protection to obtain high-quality diagnostic images. In theory, wrist radiography commonly includes anteroposterior (AP) and lateral projections; however, observations at the Radiology Installation of RSU PKU Muhammadiyah Delanggu showed that fracture examinations are generally limited to posteroanterior (PA) and lateral projections. This difference highlights a gap between theoretical recommendations and clinical practice, as several references emphasize the importance of projection variation to enhance diagnostic accuracy. This study aimed to describe the wrist joint radiographic examination procedures for fracture cases at RSU PKU Muhammadiyah Delanggu and to examine the immobilization techniques applied during the procedure. A descriptive qualitative design with a case study approach was used, conducted from May to June 2025. The subjects included three radiographers, while the object of study was wrist radiography in fracture cases. Data were obtained through direct observation, interviews, and documentation, and analyzed descriptively. The findings showed that PA and lateral projections were consistently used, with immobilization achieved using sandbags and foam pads to ensure stability and minimize motion artifacts. Radiation protection was implemented through lead aprons, collimation, and appropriate exposure adjustments. Overall, the procedures followed established radiography guidelines, particularly the Bontrager standard, ensuring both diagnostic quality and patient safety.